Relationship between sprint ability and loaded/unloaded jump tests in elite sprinters - Loturco, I.; D'Angelo, R. A.; Fernandes, V.; Gil, S.; Kobal, R.; Cal Abad, C. C.; Kitamura, K.; Nakamura, F. Y. (The Journal of Strength and Conditioning Research, 2015)
The neuromechanical determinants of sprint running performance have been investigated in team sports athletes and non-elite sprinters. The aim of this study was to quantify the relationships between kinetic and performance parameters, obtained in loaded and unloaded vertical and horizontal jumps, and sprinting in elite athletes. Twenty-two sprinters performed squat jumps, countermovement jumps, horizontal jumps, and jump squats with different loads on a force platform, in addition to a 50-m sprint. Results indicated that jumping height and distance in vertical and horizontal jumps are more strongly correlated (R2 ˜ 0.81) to sprinting speed than the respective peak forces (R2 ˜ 0.36). Furthermore, the optimum load generating the maximum power in the jump squat is also highly correlated to sprint performance (R2 ˜ 0.72). These results reveal that vertical and horizontal jump tests may be used by coaches for assessing and monitoring qualities related to sprinting performance in elite sprinters.